Covid-19 pandemic : Zainon Abdullah’s expression through artworks / Siti Humaini Said Ahmad @ Syed Ahmad and Muhamad Rozali Othman - Said Ahmad @ Syed Ahmad, Siti Humaini; Othman, Muhamad Rozali (Universiti Teknologi MARA, Perak, 2020)
The outbreak of the Covid-19 Pandemic has gravely impacted various sectors, such as the economy, tourism and education industries. It is also affecting social activities and the standards of everyday life. The effects it has on the art community includes the suspension of many art exhibitions and even the cancellation of these events when the MCO (Movement Control Order), designed to curb and contain the spread of the virus, was implemented by the government. In response, an initiative by prominent local artist Zainon Abdullah to hold a virtual exhibition of his work began. Throughout the partial lockdown, he delivers his artistic expressions through the lens of a world coloured by Covid-19. This study has identified certain themes like nature, the divine, environmental awareness, submission and resurrection in his artwork as extensions of the artist’s emotional landscape. Research concludes that this series of Zainon Abdullah’s artworks can be classified by phases wherein each phase represents a different order of shapes, meanings and messages while still operating within the restrictions of Covid-19. Thus, Zainon Abdullah’s work has become a chronologically recorded documentation of an artist’s reaction towards a momentous event in world history.